Are individual analyses of multiple short urine collections throughout the 24 hours superior to a standard 24‐hour urine collection in precipitation risk assessment of healthy subjects?. Issue 3 (25th January 2021) - Shafiee, Mohammad A.; Shaker, Pouyan; Hosseini, Sayyideh F.; Alavinia, Mohammad; Aarabi, Mehdi; Rezaee, Ali J.; Halperin, Mitchel L.
Abstract: Purpose: The commonly used 24‐hour collection technique has been the mainstay of diagnosis for supersaturation but has some certain limitations. Hence, superiority of multiple short urine collections as a new alternative in precipitation risk assessment was assessed compared to the standard 24‐hour urine collection among healthy subjects. Materials and Methods: Individual urine samples of 26 healthy subjects were acquired every 2 to 3 hours throughout the 24 hours. Urine samples were obtained and the time and volume of each sample were recorded. Urinary constituents involved in precipitation including, sodium‐potassium, chloride, calcium, phosphate, citrate, magnesium, urea, creatinine and pH were measured. A simulated 24‐hour collection was recalculated by the totalling of all shorter urine collections volume and urinary constituents excretions throughout the day. Results: Urine pH, urine creatinine and precipitation rate had a significantly lower values in 24‐hours urine collection compared to one individual value of multiple urine collections by −0.769 ( P  < .0001), −7.305 ( P  < .0001), and − 12.838 ( P  < .0001), respectively. However, calcium (2.697, P  < .0001), citrate (3.54, P  < .0001), total phosphate (19.961, P  < .0001) and total creatinine (9.579, P  < .0001) had statistically significantly higher values in the 24‐hours urine collection compared to individual value of multiple urine collections. Conclusion: Based on the results, individual analysis of multiple shorter urine collections throughout the day improves the ability of identifying supersaturation points, precipitation risk zones and may potentially improve risk assessment compared to the 24‐hour urine collection method. SUMMARY AT A GLANCE: Individual analysis of multiple shorter urine collections throughout the day improves the ability of identifying supersaturation points, precipitation risk zones and may potentially improve risk assessment compared to the 24‐hour urine collection in the assessment of the risks of stone formation.